Spatial analysis of socio-economic issues: Gender and GIS in Nepal - Brown, S. (International Mountain Society (IMS) and United Nations University, 2003)
Spatial patterns in socioeconomic data reveal issues and trends that would otherwise be missed by data aggregation to political or other units. Geographic Information System (GIS) tools provide display and analysis capabilities that are underutilized by many social scientists. The present article combines field-based surveys that maintain locational information with GIS tools to examine gender roles, responsibilities, and workloads in a spatial context for a case-study watershed in Nepal. Adult women outworked men by an average of 3.8 hours per day. Spatial differences in workloads are related to road access, with women living near the road working longer days, and men near the road participating more in typically female tasks such as collecting drinking water. Households with poor access have larger landholdings, greater total production, and are more reliant on subsistence agriculture. Households with road access use more agrochemicals, have smaller landholdings, and are more reliant on off-farm employment to meet their families' needs. GIS helps communicate these spatial trends more clearly and quantifies key issues when combined with statistical analysis. The use of field-based participatory techniques, aerial photographs and quantitative GIS and statistical analysis is infrequent in gender analysis but provides social scientists with powerful tools for investigating variability. In this study, the significant influence of the road on socioeconomic issues was highlighted, along with the need to focus development activities spatially.